(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract The aim of the research is to demonstrate the impact of long-term investment on profitability, and in order to achieve this goal, long-term investment was chosen, represented by (the ratio of long-term investments to total investments, the ratio of long-term investment to the total (deposits) as independent variables, and studying its impact on the dependent variable, which is profitability as measured by the rate of return on investments, the rate of return on equity. In order to reach the results, the inductive approach and the analytical descriptive approach were used, and the research found a significant impact of the long-term investment management of the research sample banks, in the rate of return on investments, and the rate of return on equity, and among the most prominent findings of this study of the results that the research sample banks differed among themselves in achieving the percentage of long-term investment, but it was overall Low. The reason for the decrease is due to the high-risk Iraqi environment and the banks’ reticence to exploit the funds available for investment, which led to low long-term investment rates and banking profitability.